Clinical consequences of untreated dental caries assessed using PUFA index and its covariates in children residing in orphanages of Pakistan - Ramsha Kamran; Warda Farooq; Mehreen Riaz Faisal; Faisal Jahangir (BMC, 2017)
Abstract Background The purpose of this study was to determine the prevalence and clinical effects of untreated dental caries in Pakistani children residing in orphanages using the DMFT and PUFA index; association of decay and untreated dental caries with demographics including type of orphanage; behavioural and dental visiting pattern; and association of dental pain experience and type of orphanage with dental visiting. Methods A cross-sectional survey was conducted on a total of 753 orphan children belonging to 4-17 years of age group residing in twin cities of Rawalpindi and Islamabad, Pakistan. Clinical examination of children was performed using the DMFT and PUFA index for the assessment of dental caries and untreated decay, followed by questionnaire enquiring about eating and oral hygiene habits, dental visiting pattern and dental pain and swelling experience. Association between dental decay, child's dental visiting and pain as a consequence of untreated decay was carried out using chi square test and logistic regression analysis. Results The overall caries prevalence was 34.8% and overall prevalence of PUFA/pufa was 15.9%. The mean score of DMFT and dmft was 1.18 (SD 0.39) and 1.04 (SD 0.23), and mean PUFA was 1.18 (SD 0.57) and mean pufa score 1.14 (SD 0.35). Untreated caries ratio was found to be 49.1% indicating half the decay had progressed to involve the pulp. No significant association of gender was found with DMFT, dmft, PUFA and pufa (p > 0.05), however, when analysed individually, the 'D' component of DMFT was significantly associated with male gender (p = 0.05). Furthermore, no significant association of DMFT/dmft or PUFA/pufa in either dentition was found with behavioural characteristics such as dietary and oral hygiene habits. Also, 66.2% children who experienced pain had not been to the dentist in the past year (p = 0.013) and 52.6% children who mentioned experiencing pain at night had not been to the dentist in the past year (p = 0.009). Children with decay were more likely to have visited the dentist (OR 3.3, 95% CI 1.42-7.6, p = 0.006). However, children who reported to have experienced pain were less likely to have visited the dentist in the past year (OR 0.53, 95% CI 0.32-0.88, p = 0.014). Conclusions Moderate levels of decay were found in the sample with 'd' component majorly responsible for the cumulative DMFT index. However, alarmingly almost half of the decay component (49.1%) had progressed to involve the pulp. Experiencing pain in teeth prompted dental visits. Initiation of preventive services for children residing in orphanages in Pakistan would help greatly towards reducing the burden of untreated decay.